Surface disinfection challenges for Candida auris: an in-vitro study. Issue 4 (April 2018) - Kean, R.; Sherry, L.; Townsend, E.; McKloud, E.; Short, B.; Akinbobola, A.; Mackay, W.G.; Williams, C.; Jones, B.L.; Ramage, G.
Summary: The emerging pathogenic multidrug-resistant yeast Candida auris is an important source of healthcare-associated infections and of growing global clinical concern. The ability of this organism to survive on surfaces and withstand environmental stressors creates a challenge for eradicating it from hospitals. A panel of C. auris clinical isolates was evaluated on different surface environments against the standard disinfectant sodium hypochlorite and high-level disinfectant peracetic acid. C. auris was shown to selectively tolerate clinically relevant concentrations of sodium hypochlorite and peracetic acid in a surface-dependent manner, which may explain its ability to successfully persist within the hospital environment.